2016
DOI: 10.1016/j.drugalcdep.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Proactive telephone counseling for adolescent smokers: Comparing regular smokers with infrequent and occasional smokers on treatment receptivity, engagement, and outcomes

Abstract: Background Adolescent smoking cessation efforts to date have tended to focus on regular smokers. Consequently, infrequent and occasional smokers’ receptivity and response to smoking cessation interventions is unknown. To address this gap, this study examines data from the Hutchinson Study of High School Smoking--a randomized trial that examined the effectiveness of a telephone-delivered smoking cessation intervention for a large, population-based cohort of adolescent smokers proactively recruited in an educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
1
3
0
2
Order By: Relevance
“…Within a Swedish study, more than 200,000 university students were invited to participate in a text messaging-based smoking cessation intervention via email, but fewer than 2.000 students completed the assessments and could be included within the trial. Consistent with studies on telephone-or physician-delivered advice for adolescent smoking cessation, our results underscore the importance of proactive recruitment strategies and low-threshold interventions to attain high participation rates (Heffner et al, 2016;Pbert et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Within a Swedish study, more than 200,000 university students were invited to participate in a text messaging-based smoking cessation intervention via email, but fewer than 2.000 students completed the assessments and could be included within the trial. Consistent with studies on telephone-or physician-delivered advice for adolescent smoking cessation, our results underscore the importance of proactive recruitment strategies and low-threshold interventions to attain high participation rates (Heffner et al, 2016;Pbert et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…As regard to self-reported smoking history, previous studies have indicated high reliability of self-reporting 64. In addition, occasional smokers were included in the current smoker category to capture all at-risk respondents, as infrequent and occasional smokers may still have a nicotine dependency and may under-report 65…”
Section: Discussionmentioning
confidence: 99%
“…Es importante considerar que muchos de esos usuarios incidentales son jóvenes quienes están comenzando la adicción. 22 Para la sanidad pública es redituable dirigir campañas de cesación a los jóvenes que fuman de vez en cuando, ya que algunos de ellos probablemente escalarán el uso y, eventualmente, se convertirán en fumadores diarios. 22,23 Valdría la pena generar mayor evidencia científica intentando determinar si es una etapa transicional o puede ser un patrón permanente.…”
Section: Características Asociadas a Los Fumadores Ocasionalesunclassified
“…Por último, si éstos no se encuentran interesados, el profesional de la salud debe hacer hincapié en que el tabaquismo esporádico aumenta la probabilidad de que se conviertan en consumidores diarios y elevan el riesgo de padecer una enfermedad asociada. Heffner et al 22 encontraron que jóvenes quienes fuman con diversos patrones de consumo mostraban interés similar en tratamientos de cesación y tenían una respuesta similar a la intervención. No se encontraron diferencias entre los grupos de fumadores infrecuentes, ocasionales y asiduos respecto a la receptividad y a la respuesta con una inter-vención motivacional y de entrenamiento en desarrollo de habilidades cognitivo conductuales.…”
Section: Propuesta De Intervenciónunclassified